Iowa RBA, November 30, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Email for the Iowa RBA for November 30, 1998. Highlights include Black-legged Kittiwake, Red-throated Loon, Western Grebe and Surf Scoter. Includes notes for updates for December 2, December 3, and December 5. Epson - sheet feed/flatbed